Market maturity and mispricing - Jacobs, Heiko (Journal of Financial Economics, 2016)
Relying on the Stambaugh, Yu, and Yuan (2015) mispricing score and on 45 countries between 1994 and 2013, I document economically meaningful and statistically significant cross-sectional stock return predictability around the globe. In contrast to the widely held belief, mispricing associated with the 11 long/short anomalies underlying the composite ranking measure appears to be at least as prevalent in developed markets as in emerging markets. Additional support for this conjecture is obtained, among others, from tests for biased expectations based on the behavior of anomaly spreads surrounding earnings announcements as well as from within-country variation in development.